EFFORT TO IMPROVE POETRY WRITING SKILLS FOR GRADE 5 STUDENTS THROUGH DISCOVERY LEARNING - Amalia Nugraha Fisabillila; Agung Setyawan (Citra Dharma Cindekia, 2022)
Writing is one of the most complex language skills. In the content of Indonesian in the 2013 curriculum, one way to make students think creatively is to make literary products, one of which is writing poetry. The purpose of this research is to improve students' poetry writing skills through discovery learning. The method used is descriptive qualitative method with the research design taken is the Kemmis and Mc Taggart model in the form of a spiral. This model has four components including planning, action, observation, reflection, and re-planning that aims to solve problems. From the implementation of this classroom action research, it can be concluded that using discovery learning learning models can improve students' poetry writing skills, this is evidenced by an increase from pre-cycle to cycle II with a range of completeness starting from 16%, 58%, to 96%. Discovery learning learning model can increase students' writing potential because of an active way of learning and improving student experience. The discovery learning method focuses on the real student experience so as to foster student creativity.